Prevention of Corruption in The Procurement of Goods and Services in The Government Sector - Zainab Ompu Jainah; Listia Laila Wandita (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
The procurement of goods and services encompasses several stakeholders, necessitating the establishment of ethical standards, norms, and principles to effectively control and inform the policy-making process in this domain. The objective of this study is to examine, comprehend, and analyze the execution of Article 38 in Presidential Regulation Number 12 of 2021, which pertains to the procurement of goods and services by the government through E-Purchasing. Additionally, this research aims to identify the issues that impede the effective implementation of these provisions. This study employs normative and empirical legal methodologies. The execution of Article 38 of Presidential Regulation Number 12 of 2021, which pertains to the government's procurement of goods and services through E-Purchasing, has been partially implemented but not fully optimized due to various challenges. These challenges include insufficient capacity among civil servants to meet the demands of their tasks and workload, inadequate comprehension of the primary responsibilities and functions of electronic application services, limited understanding of human resources, and insufficient supervision and guidance in the implementation of Article 38 of Presidential Regulation Number 12 of 2021.